2000
DOI: 10.1073/pnas.97.7.3544
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant rabies virus as potential live-viral vaccines for HIV-1

Abstract: Recombinant, replication-competent rabies virus (RV) vaccine strain-based vectors were developed expressing HIV type I (HIV-1) envelope glycoprotein (gp160) from both a laboratory-adapted (CXCR4-tropic) and a primary (dual-tropic) HIV-1 isolate. An additional transcription stop/start unit within the RV genome was used to express HIV-1 gp160 in addition to the other RV proteins. The HIV-1 gp160 protein was stably and functionally expressed, as indicated by fusion of human T cell lines after infection with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 38 publications
2
74
0
Order By: Relevance
“…Preclinical as well as clinical trials with these constructs yielded disappointing results as the neutralizing Abs induced by such vaccines lacked the breath to provide solid protection against different HIV-1 isolates (21,22). Subsequent vaccine efforts were directed at inducing cell-mediated immune responses (6,(23)(24)(25). Optimized DNA vaccines expressing the gag of HIV-1 provided initial protection to nonhuman primates challenged with SHIV-89.6P virus (26).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical as well as clinical trials with these constructs yielded disappointing results as the neutralizing Abs induced by such vaccines lacked the breath to provide solid protection against different HIV-1 isolates (21,22). Subsequent vaccine efforts were directed at inducing cell-mediated immune responses (6,(23)(24)(25). Optimized DNA vaccines expressing the gag of HIV-1 provided initial protection to nonhuman primates challenged with SHIV-89.6P virus (26).…”
Section: Discussionmentioning
confidence: 99%
“…For experiments involving recovery of the recombinant RVs, the previously described RV recovery system was used (9,28). Briefly, BSR T7 cells (3), which stably express T7 RNA polymerase, were transfected with 5 g of full-length RV cDNA (SPBN-333-Gag, SPBN-⌬CD-Gag, SPBN-333-⌬CD-Gag, BNSP-Gag, and BNSP) in addition to plasmids encoding the RV N, P, L, and G proteins by using a Ca 2 PO 4 transfection kit (Stratagene), as instructed by the vendor.…”
Section: Methodsmentioning
confidence: 99%
“…Several groups have attempted to develop vaccine vehicles using RV-based vectors. It has been reported that the RV vectors expressing foreign antigens induce strong humoral and cellular responses against other kinds of viral pathogens, such as human immunodeficiency virus type 1 and hepatitis C virus, in the mouse model (54,55,79,81). The high efficacy of RV in inducing an antiviral immune response may also be due to the stimulation of immunocytes by RV components.…”
mentioning
confidence: 99%